Effects of ameliorant application on the growth and yield of rice plants (Oryza sativa L.) - Arini Alfi Farhati; Dewi Firnia; Alfu Laila (Jurnal Ilmu Pertanian, 2023)
An ameliorant is a chemical that can be used to improve soil fertility. The improving agents include dolomite and steel slag. Steel slag is a by-product of the steel industry containing CaCO3, SiO2, CaSiO3, and MgO, which can be used to improve the growth and yield of rice plants. Dolomite, on the other hand, is a limestone rock containing MgO and CaO, which is useful in agricultural soils. This study aimed to determine the types and doses of ameliorants affecting the growth and yield of rice plants (Oryza sativa L.). The research was carried out at Sukadana Village, Ciomas Serang-Banten District. A non-factorial Group Randomized Design with seven treatments was employed in this investigation. The treatments include P0 = No treatment (control), P1 = 2 t/ha of dolomite, P2 = 2 t/ha of dolomite + 2.5 t/ha of steel slag, P3 = 1.5 t/ha of steel slag, P4 = 2.5 t/ha of steel slag, P5 = 5 t/ha of steel slag, and P6 = 7.5 t/ha of steel slag. Observation was made on steel slag characterization, plant height, the total number of tillers, the weight of 1000 grains, the amount of grain per clump, and the weight of dry-milled grain. The results showed that applying dolomite at 2 t/ha and steel slag at 2.5 t/ha could increase the weight of 1000 grains of rice, and applying steel slag at 1.5 t/ha could enhance the amount of grain per clump.